Unraveling the "Cuban miracle": A conversation with Dr. Enrique Beldarrain Chaple - Claudia Chaufan (Social Medicine Publication Group, 2014)
An interview with a Cuban physician and professor of Epidemiology and Anthropology at the Medical University of Havana, Cuba, unravels so-called Cuban miracle, by laying out the history and foundations of a health system built on the principles of health equity and justice. The interview traces the beginning of the system to the Cuban revolution, briefly providing the social and public health background to this revolution, elaborates on the training of medical personnel and on the Cuban state policy of medical internationalism, and underscores that achieving a modicum of health justice in Cuba's neighboring country will require freeing US health care from the chains of a profit driven system.